The Role of Mitochondria, Oxidative Stress, and the Radical-binding Protein A1M in Cultured Porcine Retina. (3rd June 2017) - Åkerström, Bo; Cederlund, Martin; Bergwik, Jesper; Manouchehrian, Oscar; Arnér, Karin; Taylor, Ingrid Holmgren; Ghosh, Fredrik; Taylor, Linnéa
ABSTRACT: Purpose : The purpose of this study was to explore the relationship between oxidative stress, antioxidant defense, mitochondrial structure, and biomechanical tissue support in the isolated porcine retina. Methods : Full-thickness retinal sheets were isolated from adult porcine eyes. Retinas were cultured for 2 or 48 h using (1) a previously established low-support explant protocol with photoreceptors positioned against the culture membrane (porous polycarbonate) or (2) a high-support procedure developed by our group, apposing the Müller cell endfeet and inner limiting membrane against the membrane. The grafts were analyzed by quantitative polymerase chain reaction (PCR), immunohistochemistry, and transmission electron microscopy (TEM), and culture medium was assayed for the cell damage and oxidative stress markers lactate dehydrogenase and protein carbonyls. Results : In explants cultured with physical support to the inner border, cone photoreceptors were preserved and lactate dehydrogenase levels were reduced, although an initial (2 h), transient, increased oxidative stress was observed. Elevated expression of the antioxidants α1 -microglobulin and heme oxygenase-1 was seen in the mitochondria-rich inner segments after 48 h compared to low-support counterparts. Housekeeping gene expression suggested a higher degree of structural integrity of mitochondria in high-support explants, and TEM of inner segments confirmed preservation of a normal mitochondrial morphology. Conclusion : Providing retinal explants with inner retinal support leads to mobilization of antioxidant proteins, preservation of mitochondrial function, and increased cell viability. Consequently, the failure of low-support retinal cultures to mobilize an adequate response to the oxidative environment may play a key role in their rapid demise. These findings shed new light on pathological reactions in biomechanically related conditions in vivo .